Siekierka miedziana z Wożuczyna w woj. zamojskim - Gurba, Jan (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
An axe with a fan – like blade, made of pure copper (99,8%), and found in the area of the Volhynian-Lublin Painted Pottery Culture and the Funnel Beaker Culture, may most probably be connected with the fromer culture.